Propolis in Oral Healthcare: Antibacterial Activity of a Composite Resin Enriched With Brazilian Red Propolis - Oliveira, José Marcos dos Santos; Cavalcanti, Théo Fortes Silveira; Leite, Ingrid Ferreira; dos Santos, Dávida Maria Ribeiro Cardoso; Porto, Isabel Cristina Celerino de Moraes; de Aquino, Fernanda Lima Torres; Sonsin, Artur Falqueto; Lins, Renata Matos Lamenha; Vitti, Rafael Pino; de Freitas, Johnnatan Duarte; Barreto, Emiliano de Oliveira; de Souza, Samuel Teixeira; et al. (Frontiers in Pharmacology, 2021)
The aim of this study was to obtain a Brazilian red propolis (BRP) enriched composite resin and to perform the characterization of its antibacterial activity, mechanical, and physical-chemical properties. Brazilian red propolis ethyl acetate extract (EABRP) was characterized by LC-ESI-Orbitrap-FTMS, UPLC-DAD, antibacterial activity, total flavonoids content, and radical scavenging capacity. BRP was incorporated to a commercial composite resin (RC) to obtain BRP enriched composite at 0.1 %, 0.15 % and 0.25 % (RP10, RP15 and RP25, respectively). The antibacterial activity RPs was evaluated against Streptococcus mutans by contact direct test and expressed by antibacterial ratio. The RPs were characterized as its cytotoxicity against 3T3 fibroblasts, flexural strength (FS), Knoop microhardness (KHN), post-cure depth (CD), degree of conversion (DC%), water sorption (Wsp), water solubility (Wsl), average roughness (Ra), and thermal analysis. Were identified 50 chemical compounds from BRP extract by LC-ESI-Orbitrap-FTMS. EABRP was bacteriostatic and bactericide at 125 µg/mL and 500 µg/mL, respectively. The RP25 exhibited antibacterial ratio of 90.76 % after 1 h of direct contact with S. mutans (p < 0.0001) while RC no showed significative antibacterial activity (p = 0.1865), both compared with cell control group. RPs and RC no showed cytotoxicity. RPs exhibited CD from 2.74 to 4.48 mm, DC% from 80.70 to 83.96 %, Wsp from 17.15 to 21.67 μg/mm3, Wsl from 3.66 to 4.20 μg/mm3, Ra from 14.48 to 20.76 nm. RPs showed thermal resistance between 448 – 455 ºC. The results support that propolis can be used on development of modified composite resins that show antibacterial activity and that have compatible mechanical and physical-chemical properties to the indicate for composite resins.